2005
DOI: 10.1038/sj.bjc.6602333
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of case–control studies on the combined effect of hepatitis B and C virus infections in causing hepatocellular carcinoma in China

Abstract: We investigated whether concurrent infection by hepatitis B virus (HBV) and hepatitis C virus (HCV) in China, a hyperepidemic area for these infections, was associated with a higher risk of causing hepatocellular carcinoma (HCC) than each infection alone in a metaanalysis in China, 32 case -control studies involving 3201 cases and 4005 controls, identified from a computer-based literature search from 1966 to 2004. The pooled odds ratio and 95% confidence interval (CI) for HBsAg positivity was 14.1 (95% CI: 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(148 citation statements)
references
References 14 publications
(18 reference statements)
3
140
1
4
Order By: Relevance
“…Among studies performed outside South Europe, a recent meta-analysis of 32 Chinese case-control studies showed a moderate synergism between the two infections for HCC risk, with ORs of 15.6 for HBsAg positivity alone, 8.1 for anti-HCV positivity alone and 35.7 for positivity for both markers (Shi et al, 2005).…”
Section: Overt Hepatitis B Virus Infectionmentioning
confidence: 99%
“…Among studies performed outside South Europe, a recent meta-analysis of 32 Chinese case-control studies showed a moderate synergism between the two infections for HCC risk, with ORs of 15.6 for HBsAg positivity alone, 8.1 for anti-HCV positivity alone and 35.7 for positivity for both markers (Shi et al, 2005).…”
Section: Overt Hepatitis B Virus Infectionmentioning
confidence: 99%
“…A serosurvey performed in China in 2006, 14 years after the introduction of vaccination against hepatitis B in infants, reported a hepatitis B surface antigen prevalence of 7.2% in participants aged 1-59 years [3]. Additional environmental risk factors have also been described in Chinese populations that affect either HCC prevalence directly or progression from hepatitis B infection to HCC.These factors include exposure to aflatoxin [4,5], contamination of drinking water with blue-green algae, nitrite or organochlorine pesticides [6], coinfection with hepatitis C virus (HCV) [7], and excessive alcohol consumption. A number of genetic polymorphisms have also been associated with the progression to HCC among persons infected with hepatitis B virus, including the susceptibility locus (rs17401966) in the kinesin family member 1B gene (KIF1B) at chromosome 1p36.22 [8], rs9272105 (HLA-DQA1/DRB1), and rs455804 (GRIK1) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Almost 12% of HCC patients have co-infection with HBV and HCV 165 . A meta-analysis concluded that HBV and HCV infections are important independent risk factors for HCC, and that dual infection with HBV and HCV is associated with a higher risk for HCC than is either infection alone, suggesting a synergism between the two 166 .…”
Section: Prevention Of Cancer Progressionmentioning
confidence: 99%